2020
DOI: 10.1186/s12883-020-01992-x
|View full text |Cite
|
Sign up to set email alerts
|

Application of spectral CT in the diagnosis of contrast encephalopathy following carotid artery stenting: a case report

Abstract: Background Contrast encephalopathy is a rare complication of carotid artery stenting (CAS). Contrast encephalopathy is a diagnosis of exclusion that often needs to be distinguished from high perfusion syndrome, cerebral haemorrhage, subarachnoid haemorrhage (SAH), cerebral infarction and so on. Case presentation In this study, we report on a 70-year-old man who was admitted to the hospital with transient ischaemic attacks presenting paroxysmal weakness of limbs in the previous 2 years. He had severe stenosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Following thrombectomy, there is a risk of brain tissue ischemia–reperfusion injury, as well as stress-induced immune responses triggered by surgery and contrast agents. In a separate study, a rare complication of contrast agent encephalopathy was observed after carotid artery stent surgery ( 23 ). The underlying pathogenesis of this complication is currently unclear, but it may be associated with chemical toxicity and brain edema caused by the passage of contrast agents through the blood–brain barrier ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following thrombectomy, there is a risk of brain tissue ischemia–reperfusion injury, as well as stress-induced immune responses triggered by surgery and contrast agents. In a separate study, a rare complication of contrast agent encephalopathy was observed after carotid artery stent surgery ( 23 ). The underlying pathogenesis of this complication is currently unclear, but it may be associated with chemical toxicity and brain edema caused by the passage of contrast agents through the blood–brain barrier ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a separate study, a rare complication of contrast agent encephalopathy was observed after carotid artery stent surgery ( 23 ). The underlying pathogenesis of this complication is currently unclear, but it may be associated with chemical toxicity and brain edema caused by the passage of contrast agents through the blood–brain barrier ( 23 ). All of these factors have the potential to alter the patient’s immune and inflammatory response, thus promoting the occurrence of SAP.…”
Section: Discussionmentioning
confidence: 99%